Detecção da Nosema spp. e da Varroa destructor em colmeias de Apis mellifera no semi-árido nordestino - Paiva, Charle da Silva (2014)
The Nosemosis is today one of the major threats to profitable beekeeping, just after varroa. Since it is a disease which has only recently become aware of the scientific community, the lack of knowledge and often a carelessness among beekeepers. Therefore this study aimed to detect the pathogen Nosema spp. and the V. destructor mite in non-fed and fed beehives " pollen dust" during the period of low rainfall. The experiment was conducted from June to December 2013, in the city of Jaguaruana, Ceará, where the installation of beehives and collecting bees occurred since the second stage was performed in city of Mossoró RN, which took place in the laboratory mite count and detection of Nosema spp. The data gathered from Nosema spp. and Varroa destructor infestation were statistically analyzed by using the program "R software version 2.3.0." The results showed that when comparing between beehives fed and not fed to the presence of Nosema spp. in honeybees collected inside and outside the beehives, there was no difference between treatments. As well as showed no statistics regarding the collection site differences of the bees. It was also found that the level of infestation of the mite Varroa destructor did not influence the level of presence of Nosema spp., when compared to beehives fed and not fed. However, we can not affirm that the "pollen dust" under the experimental conditions, is not a source of contamination, since the Nosema spp. can develop at higher temperatures